PROTECTION OF PERSONAL DATA ON WHATSAPP IN THE PERSPECTIVE OF LAW NO. 19 OF 2016 ABOUT ELECTRONIC INFORMATION AND TRANSACTION (ITE) - Kirana, Yanti; Basyarudin (Sekolah Tinggi Ilmu Hukum Awang Long, 2021)
Rapid technological progress in the field of communication has led to many innovations and new ideas, ideas that aim to make the process of human communication more effective. One innovation that facilitates the communication process is a cell phone or commonly abbreviated with the word mobile. The emergence of various smartphones such as Blackberry, Android, Iphone, Windows Phone and Symbian S60 is an example of technological sophistication in the form of cellphones. From the various types of smartphones that are available, many of them offer advanced application features such as the instant messenger service application,